Biotransformation and Biological Interaction of Graphene and Graphene Oxide during Simulated Oral Ingestion. Issue 24 (14th May 2018) - Guarnieri, Daniela; Sánchez‐Moreno, Paola; Del Rio Castillo, Antonio Esaú; Bonaccorso, Francesco; Gatto, Francesca; Bardi, Giuseppe; Martín, Cristina; Vázquez, Ester; Catelani, Tiziano; Sabella, Stefania; Pompa, Pier Paolo
Abstract: The biotransformation and biological impact of few layer graphene (FLG) and graphene oxide (GO) are studied, following ingestion as exposure route. An in vitro digestion assay based on a standardized operating procedure (SOP) is exploited. The assay simulates the human ingestion of nanomaterials during their dynamic passage through the different environments of the gastrointestinal tract (salivary, gastric, intestinal). Physical–chemical changes of FLG and GO during digestion are assessed by Raman spectroscopy. Moreover, the effect of chronic exposure to digested nanomaterials on integrity and functionality of an in vitro model of intestinal barrier is also determined according to a second SOP. These results show a modulation of the aggregation state of FLG and GO nanoflakes after experiencing the complex environments of the different digestive compartments. In particular, chemical doping effects are observed due to FLG and GO interaction with digestive juice components. No structural changes/degradation of the nanomaterials are detected, suggesting that they are biopersistent when administered by oral route. Chronic exposure to digested graphene does not affect intestinal barrier integrity and is not associated with inflammation and cytotoxicity, though possible long‐term adverse effects cannot be ruled out. Abstract : The biotransformation and biological impact of few layer graphene and graphene oxide are analyzed through an in vitro digestion assay. No structural changes/degradation of the nanomaterials are detected, suggesting that they are biopersistent when administered by oral route. Digested graphene does not induce inflammation and cytotoxicity on intestinal barrier, though long‐term effects cannot be ruled out.